KEKUATAN HUKUM PEMBUKTIAN REKAM MEDIS KONVESIONAL DAN ELEKTRONIK BERDASARKAN HUKUM POSITIF INDONESIA - Chris Anggi Natalia Berutu; Yanti Agustina; Sonya Airini Batubara (Jurnal Hukum Samudra Keadilan, 2020)
Medical records are files containing patient records, which are made chronological time. There are two types of medical records and in general have been regulated in Permenkes Number 269 / MENKES / PER / III / 2008 concerning Medical Records, namely conventional medical records and electronic medical records. One of the benefits of medical records is as evidence in the law enforcement process. This type of research is normative juridical research and is analytical descriptive in nature. The data source used in this research is secondary data, which is obtained from books, journals, expert opinions and others. The data collection technique used is to collect data in this study through documentation studies in the form of data collection from literature or scientific writing in accordance with the object under study. Data analysis is data obtained and then analyzed qualitatively. From the study it is concluded that the difference in the strength of evidence lies in the non-fulfillment of the requirements of electronic medical records as written / letter evidence, in accordance with the Criminal Code Book 4, Concerning Evidence and Expiration, Second Chapter on Evidence by Writing and KUHAP Article 184 paragraph (1) letter c and d, as well as Articles 187 and 188 paragraph (2) letter b. This means that conventional medical records can be used as original written evidence, whereas electronic medical records cannot. The cause of the difference is because both the Criminal Code and the Criminal Procedure Code, the power of written evidence, is only in writing, in the form of original letters and / or authentic deeds. The data used are (1) primary data in the form of statutory regulations, results of interviews with hospitals and courts, (2) secondary data through literature studies of various laws and regulations and books / journals to obtain expert opinion. The results of this research are expected to be published through (1) scientific articles in Accredited National Journals and (2) teaching materials in Law courses at the Faculty of Law at Prima Indonesia University.